Dampak Perkebunan Terhadap Pertumbuhan Ekonomi dan Kemiskinan Di Sumatera Utara - Mangasi Sinurat; Cia Cai Cen (Jurnal Pasar Modal dan Bisnis, 2019)
This aim of this study is to prove the impact of plantation industries on economic growth and poverty in North Sumatra. Using path analysis and 66 pooled data, the results are obtained: Oil Palm, Rubber and Coconut Plantation partially positive and significant impact the Economy growth in North Sumatra, whereas Oil Palm Plantation, Rubber, Coconut and Economy growth are not partially significant negative towards Poverty in Sumatra North, then the economy growth is not able to mediate the relationship between Palm Oil, Rubber and Coconut against Poverty in North Sumatra. The government needs to implement the new policies such as downstream processing of plantation products so that it will not be only accepted by few people.